Protein-protein interactions and metabolite channelling in the plant tricarboxylic acid cycle - Zhang, Y; Beard, K; Swart, C; Bergmann, S; Krahnert, I; Nikoloski, Z; Graf, A; Ratcliffe, R; Sweetlove, L; Fernie, A; Obata, T (Nature Publishing Group, 2017)
Protein complexes of sequential metabolic enzymes, often termed metabolons, may permit direct channeling of metabolites between the enzymes, providing increased control over metabolic pathway fluxes. Experimental evidence supporting their existence in vivo remains fragmentary. In the present study, binary interactions of the proteins constituting the plant tricarboxylic acid (TCA) cycle are tested. Affinity purification-mass spectrometry, split-luciferase and yeast-two-hybrid assays are employed and the (semi-)quantitative results from these methods are integrated to generate a single reliability score for assessing protein-protein interactions. By this approach, 158 interactions including those between the catalytic subunits of sequential enzymes and many novel interactions between subunits of enzymes mediating non25 adjacent reactions are identified. Channeling of citrate and fumarate in isolated potato mitochondria are revealed by isotope dilution experiments. These results provide the evidence for a functional TCA cycle metabolon in plants which we discuss in the context of contemporary understanding of this pathway in other kingdoms.